Nanocrystals based pulmonary inhalation delivery system: advance and challenge - Pengfei Yue; Weicheng Zhou; Guiting Huang; Fangfang Lei; Yingchong Chen; Zhilin Ma; Liru Chen; Ming Yang (Taylor & Francis Group, 2022)
Pulmonary inhalation administration is an ideal approach to locally treat lung disease and to achieve systemic administration for other diseases. However, the complex nature of the structural characteristics of the lungs often results in the difficulty in the development of lung inhalation preparations. Nanocrystals technology provides a potential formulation strategy for the pulmonary delivery of poorly soluble drugs, owing to the decreased particle size of drug, which is a potential approach to overcome the physiological barrier existing in the lungs and significantly increased bioavailability of drugs. The pulmonary inhalation administration has attracted considerable attentions in recent years. This review discusses the barriers for pulmonary drug delivery and the recent advance of the nanocrystals in pulmonary inhalation delivery. The presence of nanocrystals opens up new prospects for the development of novel pulmonary delivery system. The particle size control, physical instability, potential cytotoxicity, and clearance mechanism of inhaled nanocrystals based formulations are the major considerations in formulation development.